Novel concept for THz signals generation in heterostructures - Ong, Duu Sheng; Hartnagel, Hans L. (WILEY-V C H VERLAG GMBH, 2007)
We demonstrate by a Monte Carlo simulation that the reflection of quasi-ballistically accelerated electrons at the interfaces of an In(0.52)A(0.48)As/In0.53Ga0.47As/In0.52Al0.48As double-heterojunction structure is able to generate current oscillations at frequencies in the THz range, The possibility of taking advantage of this mechanism to generate THz signals has been demonstrated in structures with well dimension close to the electron ballistic transport length in In0.53Ga0.47As.